Quality assurance and certification in ecotourism (Ecotourism book series, 2007)
This book explores solutions to the problems of inconsistency and even exploitation of the term ecotourism through examples, case studies, and a discussion of quality control and certification. The first part of the book (chapters 2-8) moves the reader through the spectrum of quality assurance tools, from what are perceived to be the least rigorous and effective (awards of excellence and codes of conduct) to more formal, credible and effective methods (certification and accreditation), with a brief foray into using indicators to measure and monitor effectiveness. The second part (chapters 9-23) looks at a range of ecotourism stakeholders' perspectives, with an emphasis in one way or another on various industry certification programmes. A concluding chapter explores the challenges and issues for quality in ecotourism. The book has a glossary and a subject index.